Donor Factors Affecting Short Term Graft Outcome in Live Donor Kidney Transplantation - Nepali, Rabin; Shah, Dibya S; Gyawali, Prem R; Sharma, Uttam; Chalise, Pawan R. (Journal of Institute of Medicine Nepal, 2019)
Introduction: Since the beginning of renal transplant, the objective has been to increase the patient and graft survival, both short term and long term. Data relating to donor factors affecting short term survival at 6 months in live donor kidney transplantation has been scarce. This single center study tries to examine the predictors of short term graft outcome at six months in recipients of live donor kidney transplants and explore which donor characteristics are the most useful in predicting the post-transplant graft function in Nepalese population.Methods: All patients who underwent kidney transplantation between May 2015 to July 2016 were included in the study. The patients who expired during follow were excluded. The clinical and laboratory parameters of the donors we rerecorded. The recipients were followed up for six months post transplantation. The eGFR of the recipients and the occurrence of rejection were recorded at the end of six months post transplantation.Results: A total of 82 donor-recipient pairs underwent living donor renal transplantation at our hospital during the studyperiod. One recipient who expired during follow up was excluded. The mean age of donor was 45.20 ± 11.226 years of which 55 (67.9%) were female and 26 (32.1 %) were male. The mean eGFR of the donor calculated from Cockcroft Gault equation was 81.98 ± 18.11. The eGFR of the recipient at the end of six months post transplantation calculated form the MDRD equation was 67.76 ± 20.94. A total of 7 patients (8.6%) had rejection that were biopsy proven. Only donor eGFR was found to be significantly associated with eGFR of the recipient at six months post transplantation (p=0.034). Body mass index of the donor was significantly associated with rejection in the recipient at six months post transplantation (p=0.011).Conclusion:  Our study demonstrates that the donor eGFR and body mass index are independent and important factors affecting the short term graft outcome at six months post transplantation.